Strategi Pemasaran Sekolah: Analisis Pengaruh Brand Image, Digital Marketing, dan Word of Mouth terhadap Keputusan Pilihan Siswa - Karina Putri; Adimas Rois Adnan; Adi Artino (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of Brand Image, Digital Marketing, and Word of Mouth (WOM) on students' decisions in choosing a school. In an increasingly competitive digital era, these three variables are considered essential in shaping perceptions and influencing prospective students' choices. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to student respondents and analyzed using validity tests, reliability tests, and classical assumption tests. The results show that all three independent variables significantly influence school choice decisions, both partially and simultaneously. WOM is found to be the most dominant factor affecting students' decisions, followed by Brand Image and Digital Marketing. The Adjusted R Square value of 0.622 indicates that 62.2% of the variation in student decisions can be explained by these three variables. These findings imply that educational institutions should focus their marketing strategies on strengthening word-of-mouth communication, building a positive brand image, and optimizing digital media to reach prospective students effectively.